VARIASI MENU À LA CARTE DAN KEPUASAN TAMU DI KAMPUNG RESTAURANT, HYATT REGENCY KUANTAN RESORT - Susy Christina Banjarnahor; Aziza Fazira; Christine Vandika (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study evaluates the variety of à la carte menus and their impact on guest satisfaction at Kampung Restaurant, Hyatt Regency Kuantan Resort, Pahang, Malaysia. The role of the Food and Beverage department is highly strategic in creating a holistic guest experience, particularly in distinguishing the preferences and consumption patterns between short-stay and long-stay guests. Long-stay guests, such as U.S. Army personnel on duty for months, are prone to menu fatigue if the menu variety is not updated regularly. In contrast, short-stay guests tend to view menu variety as an initial attraction. Therefore, the main objective of this study is to analyze in-depth how menu diversity, innovation, and availability affect overall customer satisfaction. The method used in this research is a descriptive qualitative approach with a case study design. Data collection was carried out through direct observation, documentation, and in-depth interviews with the restaurant's operational ranks, such as the Head Chef, Sous Chef, Outlet Manager, and Assistant Outlet Manager, as well as 16 restaurant guests. Data analysis adopted the Miles, Huberman, and Saldaña model, which includes the stages of data reduction, data display, and conclusion drawing. The results indicate that the menu diversity indicators at Kampung Restaurant have not fully met guest expectations. Although the main menu and the combination of local and international ingredients are quite good, there are weaknesses in the minimal number of menu choices per category, the lack of seasonal menu innovation, and the limited options for specific dietary needs, such as vegetarianism. The evaluation of guest satisfaction shows that 81.3% of guests were disappointed with the limited menu choices, and 93.8% expected the addition of innovative menu variations, such as seafood and international dishes. This inconsistency in menu variety and availability contributes to low intention to revisit and the emergence of negative reviews, even though staff service and the restaurant atmosphere are rated very positively. In conclusion, the management of Kampung Restaurant needs to design sustainable menu innovations, improve the consistency of ingredient availability, and adjust recipes based on guest preferences to enhance satisfaction, foster long-term loyalty, and strengthen the hotel's positive image.